Production and properties of functionally graded hybrid composites containing Al3Ti and TiB2 - Savas, Omer (WALTER DE GRUYTER GMBH, 2020)
This study examined the production and properties of functionally graded hybrid composites containing titanium diboride (TiB2) and titanium tri-aluminate (Al3Ti) particles. The composites were produced by the centrifugal solid particle method at 850 degrees C. A detailed study of the microstructures, hardness and abrasive wear behavior of the hybrid composites was carried out. The results showed that the produced composites had three different regions along the centrifugal force direction. It was found that there were Al3Ti particles in the outer region, TiB2 particles in the middle region and neither Al3Ti nor TiB2 particles in the inner region of the functionally graded composites. It was determined that the abrasive wear properties of the composites were improved by 5 times with about 33 wt.% Al3Ti and by 3 times with about 7 wt.% TiB2 in comparison to the pure aluminum matrix.
Keywords: Wear; Functionally graded composite; Hybrid composites; TiB2; Al3Ti; METAL-MATRIX COMPOSITES; ABRASIVE WEAR BEHAVIOR; ALUMINUM-ALLOY; SITU; FABRICATION; Metallurgy & Metallurgical Engineering